Pengaruh Pengungkapan Environmental, Social, Dan Governance Terhadap Nilai Perusahaan - Novrianti Manulang; Harry Z. Soeratin (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosure on the value of companies listed on the Indonesia Stock Exchange. ESG is an important indicator that reflects a company's commitment to sustainability and social responsibility, which can influence investor perceptions of the company's performance. This research uses a quantitative approach with a case study method on several companies listed on the IDX. The data used in this study includes annual reports and sustainability reports of the companies, as well as relevant financial data. The results of the analysis show that better ESG disclosure can increase the value of the company, primarily through an improvement in the company's image in the eyes of investors. The environmental dimension (Environmental) has a significant impact on company value, followed by the social (Social) and governance (Governance) aspects. The study also finds that companies that are more transparent in their ESG disclosures tend to have better access to capital and demonstrate more stable and sustainable financial performance. These findings indicate that ESG disclosure can be an important factor in corporate management strategies to enhance attractiveness in the stock market and strengthen the company's reputation. This research contributes to the development of literature in the field of corporate management, particularly in the context of sustainability and corporate governance in Indonesia.